Does the Electricity Sector in 2050 Belong to Solar Power? A Case Study on Portugal - De Oliveira Loureiro, Maria (My University, 2020)
Southern European countries, such as Portugal, can successfully use solar power to meet their climate targets given their favorable exposure to insolation. Solar power is a variable renewable energy source (VRES). Consequently, other electricity generation sources and energy storage technologies become important to work in harmony with solar power to ensure a resilient electricity system. This thesis considers the year 2050 and Portugal as basis of its assumptions. Further, it uses a green-field investment model to outline which uncertainties are associated with solar becoming the major source of energy in the electricity sector in 2050. Additionally, it investigates how solar power being the major electricity supplier in the electricity sector influences the system Levelized Cost of Electricity (LCOE). An extensive sensitivity analysis, by performing a Monte Carlo analysis, evaluates different uncertainties correlated with different technologies’ development: investment and fuel costs. Also different scenarios are studied to better understand how different uncertainties impact the optimal share of solar power. These scenarios include expensive battery storage, carbon capture and storage (CCS) technologies, and an addition of hydrogen demand. The results show that solar power, despite of being primarily influenced by the solar power investment cost, is also impacted by the investment cost of battery storage. When battery storage investment costs is, on average, lower than 91 EUR/KWh, solar power becomes the major electricity generation source of the electricity sector when the solar power investment cost is lower than 650 kEUR/MW. Still, at times when the demand cannot be met by only solar power and the excess energy stored in batteries, wind power, CCS technologies, and biogas power plants become important. Nuclear power becomes extremely important at times when solar power is frequently complemented. The system LCOE, from decreasing the solar power investment cost from 800 kEUR/MW to 200 kEUR/MW is reduced by 24%, reaching a lowest of 48 EUR/MWh. CCS technologies promote an increase in system LCOE by 4 EUR/MWh, while adding a demand for hydrogen lowers system LCOE by 2 EUR/MWh.
Keywords: Carbon Capture and Storage (CCS); Expensive Battery Storage; Hydrogen Demand; Monte Carlo Analysis; System Levelized Cost of Electricity (LCOE)